2003
DOI: 10.1086/375346
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus–1 RNA Levels and CD4 Lymphocyte Counts, during Treatment for Active Tuberculosis, in South African Patients

Abstract: During 6 months of treatment, we measured human immunodeficiency virus (HIV)-1 virus loads, CD4 T cell counts, and immune activation markers, in 111 HIV-1-infected patients with active tuberculosis (TB). The median virus load (baseline, 5.58 log(10) copies/mL) significantly increased at 1 month (5.71 log(10) copies/mL), then returned to near-baseline levels at 3 months (5.40 log(10) copies/mL) and at 6 months (5.36 log(10) copies/mL). In contrast, the median CD4 counts increased at 1 month (186/mm(3)), at 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 25 publications
7
42
4
Order By: Relevance
“…In a study of patients with HIV-1/TB coinfection in the United States, TB-related increases in HIV-1 RNA in plasma decreased after 6 months of antituberculosis treatment (11). In contrast, in a more recent study from South Africa, in subjects with both pulmonary and extrapulmonary TB, inclusive of all levels of CD4 counts, HIV-1 viral loads remained elevated and CD4 counts did not improve after successful antituberculous treatment (19). Sustained activation of the immune system was demonstrable in HIV-1/TB-coinfected patients despite successful antituberculous therapy in this study (19).…”
Section: Tuberculosis (Tb) Is the Most Common Life-threatening Infectcontrasting
confidence: 82%
“…In a study of patients with HIV-1/TB coinfection in the United States, TB-related increases in HIV-1 RNA in plasma decreased after 6 months of antituberculosis treatment (11). In contrast, in a more recent study from South Africa, in subjects with both pulmonary and extrapulmonary TB, inclusive of all levels of CD4 counts, HIV-1 viral loads remained elevated and CD4 counts did not improve after successful antituberculous treatment (19). Sustained activation of the immune system was demonstrable in HIV-1/TB-coinfected patients despite successful antituberculous therapy in this study (19).…”
Section: Tuberculosis (Tb) Is the Most Common Life-threatening Infectcontrasting
confidence: 82%
“…We observed that HIV-1 individuals with active pulmonary tuberculosis displaying increased CCR5 (p= 0.0364, Figure 3b) and not CXCR4 (p=0.1914, Figure 4b) expression per cell (MFI) on CD4 T-cells when compared with HIV-1 subjects with similar CD4 count (<250 cells/ μl) suggesting preferential utilization of CCR5 rather than CXCR4 by virus in co-infected individuals. This falls in line with reports which demonstrated that R5 viral variants were preferentially recovered from patients with active TB [37]. Furthermore, increased frequency of CD4 cells expressing CCR5 and up-regulated expression limited to CD25 high and CD25 intermediate populations only in co-infected individuals with no significant change in CD25 low/negative subpopulation indicated the influence of MTB on these two subpopulations only making them more vulnerable to HIV-1 infection.…”
Section: Cd25supporting
confidence: 91%
“…It is thought that the increased proinflammatory response with active TB plays a role in increasing HIV transcription, as higher levels of tumor necrosis factor alpha (TNF-␣) are associated with higher viral loads in patients coinfected with HIV and TB (245). On the other hand, the treatment of active TB did not show a significant difference of CD4 counts or HIV viral load in a prospective cohort of 111 TB-HIV-coinfected patients in South Africa (197).…”
Section: Effect Of Tuberculosis On Hivmentioning
confidence: 99%